Factors Influencing Tax Compliance of Small and Medium Enterprises in Ghana - Kuug, S. N. (University of Ghana, 2016)
Countries all over the world depend on taxation as a means of generating the requisite resources to meet expenditure requirements. Among the contributors to the tax revenue are businesses in the private sectors which largely consists of small and medium sized enterprises. Although most businesses especially the small and medium sized enterprises are non-compliant with tax laws in Ghana, there is evidence that there are a few SMEs who try to pay their quota to the state every year. This study therefore sought to among others identify the factors that made these ‘good’ SMEs comply with the tax laws with the aim of increasing voluntary tax compliance among these entities. A questionnaire was administered to gather data from respondents made up of 500 small taxpaying units and medium taxpaying units selected from 3 regions in the country. In addition to this, an interview guide was used to gather information from the management and staff of GRA. The results indicated that capital structure, compliance cost, tax rates, tax audits and morals of taxpayers significantly influenced tax compliance. The GRA also indicated that unions and associations of businesses could help increase voluntary tax compliance of SMEs. The study recommends among others that an in-depth interview is used in future studies to enable the researcher to interview owners and managers of SMEs on the factors that influence the tax compliance behaviour of these entities. Also, policy developers should endeavor to make tax systems less complex and less costly to encourage SMEs to comply with tax requirements.
Theses (MPhil.) - University of Ghana, 2016